3D imaging, registration, and analysis of the early mouse embryonic vasculature. Issue 5 (27th March 2013) - Anderson, Gregory A.; Wong, Michael D.; Yang, Jian; Henkelman, R. Mark
<x xml:space="preserve">Abstract</x> Background: Cardiovascular development requires the input of a large number of molecular signaling molecules, and undergoes tightly regulated, three‐dimensional developmental patterning. Conventional developmental biology techniques have successfully identified many of the signaling cascades and molecular cues necessary for proper cardiovascular development, which has furnished us with a wealth of biochemical, molecular, and biologically functional information on how tightly linked cardiac and vascular development are. Still missing, however, is a genuine appreciation of the three‐dimensional (3D) nature of these important developmental steps. Results: Optical projection tomography (OPT) is a 3D imaging technique that allows for high‐resolution imaging of early mouse embryos and their developing cardiovascular systems when a PECAM‐1 antibody stain is used to highlight the vascular branching. Reported here is a method in which several 3D images of mouse embryo vasculatures can be registered, thus allowing for analysis of within‐strain variance between genetically identical mouse pups. Post‐registration, small differences in somitogenesis and ventricular trabeculation patterning can be visualized in mouse pups that differ by as little as a few hours of gestational time. Additionally, similarity metrics (cross‐correlation values) can be calculated to quantify similarities and differences. Two different mouse strains are analyzed (C57Bl/6 and CD‐1), and similar results are recognized in each strain. Conclusions: Visualizing the cardiovascular system in such a precise 3D manner allows for more accuracy in describing the steps that take place during cardiovascular development. This novel method will be applicable to many developmental biology questions in other organ systems and other species. Developmental Dynamics 242:517–528, 2013. © 2013 Wiley Periodicals, Inc.